Two parametric cell cycle analyses of plant cell suspension cultures with fragile, isolated nuclei to investigate heterogeneity in growth of batch cultivations. Issue 6 (17th December 2015) - Haas, Christiane; Hegner, Richard; Helbig, Karsten; Bartels, Kristin; Bley, Thomas; Weber, Jost
ABSTRACT: Plant cell suspensions are frequently considered to be heterogeneous with respect to growth in terms of progression of the cells through the cell cycle and biomass accumulation. Thus, segregated data of fractions in different cycle phases during cultivation is needed to develop robust production processes. Bromodeoxyuridine (BrdU) incorporation and BrdU‐antibodies or 5‐ethynyl‐2′‐deoxyuridine (EdU) click‐it chemistry are frequently used to acquire such information. However, their use requires centrifugation steps that cannot be readily applied to sensitive cells, particularly if nuclei have to be extracted from the protective cellular milieu and envelopes for DNA analysis. Therefore, we have established a BrdU‐Hoechst stain quenching protocol for analyzing nuclei directly isolated from delicate plant cell suspension cultures. After adding BrdU to test Harpagophytum procumbens cell suspension cultures the cell cycle distribution could be adequately resolved using its incorporation for the following 72 h (after which BrdU slowed biomass accumulation). Despite this limitation, the protocol allows resolution of the cell cycle distribution of cultures that cannot be analyzed using commonly applied methods due to the cells' fragility. The presented protocol enabled analysis of cycling heterogeneities in H. procumbens batch cultivations, and thus should facilitate process control of secondary metabolite production from fragile plant in vitro cultures. Biotechnol. Bioeng. 2016;113: 1244–1250. © 2015 Wiley Periodicals, Inc. Abstract : Heterogeneities in proliferation activity of a Harpagophytum procumbens cell suspension in batch culture were investigated by a newly developed flow cytometry method that allows proliferation studies on plant in vitro cultures which are very sensitive to chemical and physical treatments. Strong differences in proliferation activity throughout the cultivation time were detected that are not reflected in the course of biomass evolution. Further, the inhibition of the tracer BrdU on growth—in terms of dry mass accumulation and respiratory activity—was quantified.